Diseño e implementación de un prototipo para monitoreo veterinario de signos vitales y rastreo de mascotas empleando la tecnología LoRaWAN en el Centro Clínico Veterinario “Vida y Salud” - Arévalo Ocaña, Alex Dario (2025)
Dogs often require remote monitoring of their physiological parameters and location, necessitating the development of appropriate tools. To address this need, this research presents a veterinary monitoring prototype. This system integrates biomedical sensors and a geolocation module utilizing LoRaWAN technology. The prototype consists of an adjustable mesh vest designed to house the transmitter and its sensors. Specifically, a MAX30102 sensor continuously measures heart rate and SpO2, an MLX90614 sensor monitors body temperature, and an MPU6050 tracks the pet’s activity. A GPS module is also incorporated for real-time location tracking. An ESP32 processes all captured data, where it is verified, filtered, and organized before transmission via LoRaWAN. The receiver then captures this information, which is stored on the Firebase platform and made accessible through a mobile application developed in Android Studio. This facilitates real-time monitoring of the pet’s physiological state and location. To evaluate the prototype’s performance, tests were conducted at a veterinary clinic. Measured data were compared against those from a certified veterinary device. Furthermore, location tests were performed, with recorded geographic coordinates subsequently verified using Google Maps. The study involved ten canines, yielding 1200 vital sign measurements and 16 latitude and longitude data points for geolocation, all of which underwent statistical analysis. Statistical analysis revealed a strong correlation between the data collected by the prototype and that from the certified veterinary device, demonstrating the prototype’s efficient measurement of vital signs and location. This confirms the prototype’s reliability for remote monitoring. Moreover, the use of LoRaWAN technology proved beneficial due to its wide coverage and low power consumption, enhancing communication capabilities.